2020
DOI: 10.3390/ani10020331
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sheep Milk Extracellular Vesicle-miRNA by Sequencing and Comparison with Cow Milk

Abstract: Milk can mediate maternal-neonatal signal transmission by the bioactive component extracellular vesicles (EVs), which select specific types of miRNA to encapsulate. The miRNA profiling of sheep milk EVs was characterized by sequencing and compared with that of cow milk. Nanoparticle tracking analysis revealed that the concentration of sheep milk EVs was 1.3 ± 0.09 × 1012 particles/mL and the diameter was peaked at 131.2 ± 0.84 nm. Sheep milk EVs contained various small RNAs, including tRNA, Cis-regulatory elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
0
21
1
1
Order By: Relevance
“…Several review articles on milk-derived EV nucleic acid cargoes are available, which include their functional implications [ 61 , 163 , 164 ] and future applications [ 165 , 166 ]. Additionally, with development in the application of next-generation sequencing (NGS), several nucleic acid profiling studies (with an emphasis on miRNA) have reported their findings from milk-derived EVs in humans [ 167 , 168 , 169 , 170 , 171 , 172 , 173 ], cows [ 158 , 174 , 175 , 176 , 177 , 178 , 179 ], pigs [ 129 , 170 , 180 , 181 ], sheep [ 182 ], and buffaloes [ 183 ]. In silico insights from these data suggest potential regulation of several key pathways, but for the most part, these predictions have not been validated in vitro or in vivo.…”
Section: Milk-derived Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several review articles on milk-derived EV nucleic acid cargoes are available, which include their functional implications [ 61 , 163 , 164 ] and future applications [ 165 , 166 ]. Additionally, with development in the application of next-generation sequencing (NGS), several nucleic acid profiling studies (with an emphasis on miRNA) have reported their findings from milk-derived EVs in humans [ 167 , 168 , 169 , 170 , 171 , 172 , 173 ], cows [ 158 , 174 , 175 , 176 , 177 , 178 , 179 ], pigs [ 129 , 170 , 180 , 181 ], sheep [ 182 ], and buffaloes [ 183 ]. In silico insights from these data suggest potential regulation of several key pathways, but for the most part, these predictions have not been validated in vitro or in vivo.…”
Section: Milk-derived Evsmentioning
confidence: 99%
“…In silico comparison of the top 20 expressed miRNA in both milks that have immune-related functions. [ 182 ] Exosome Human qPCR, NGS Identified 221 and 48 mature miRNAs (fresh and 4-week-old milk stored at 4 °C, respectively) detected in 1 mL samples. No reliable detection of miRNAs in infant formula.…”
Section: Milk-derived Evsmentioning
confidence: 99%
“…Human milk exosomes were first described in 2007. To date, exosomes have been isolated (chronologically) from human [ 5 ], bovine [ 6 ], porcine [ 7 ], wallaby [ 8 ], camel [ 9 ], rat [ 10 ], horse [ 11 ], panda [ 12 ], yak [ 13 ], sheep [ 14 ], and goat milk [ 15 ]. Databases provide more than 100 articles on exosomes and other milk vesicles (more than half of them are on human and cow milk vesicles).…”
Section: Introductionmentioning
confidence: 99%
“…EVs have been identified in human [ 4 , 5 , 6 , 7 ], bovine [ 7 , 8 , 9 ], sheep [ 10 ], camel [ 11 ], and porcine milk [ 12 ]. Additionally, commercial, processed bovine milk has been shown to contain intact EVs with a content of miRNA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%